Uncertainty quantification for the representative volume element of geometrically monoclinic 3D printed concrete. (September 2021) - Wu, Yu-Ching; Yang, Qianfan; Kong, Xiangrui; Zhi, Peng; Xiao, Jianzhuang
Abstract: 3D concrete printing technology has been well developed and applied in various engineering fields. Anisotropy is one of the most important properties for the 3D printed cementitious material. Like fiber reinforced composite matters, if the material property is symmetric in only one plane, then the material is called as monoclinic with 13 independent elastic moduli in its constitutive law. In this study, multiscale finite element analysis of the monoclinic 3D printed cementitious material is made. Both material and geometrical randomness and uncertainty are quantified and investigated. At micro scale the material randomness is explored using nanoindentation technique. In addition, the geometrical uncertainty is analyzed through multiscale finite element method at meso scale. Then a stochastic finite element numerical experiment of 3D printed concrete simple supported beam under vertical loading is made based on the 13 independent stochastic elastic constants at macro scale. Computational methods proposed in this paper could be widely applied in 3D concrete printing industry.